2019
DOI: 10.1021/acsomega.9b01655
|View full text |Cite
|
Sign up to set email alerts
|

Superswelling Hybrid Sponge from Water Glass for Selective Absorption of Crude Oil and Organic Solvents

Abstract: A lightweight super hydrophilic hybrid sponge is designed and demonstrated out of water glass and an organic polymer, which has a macroporous flaky nature and is superflexible with an apparent density of 0.069 g cc–1, ∼97% porosity, and 3000% water uptake. The octadecyltrimethoxy silane-modified hybrid sponge exhibits selective absorption of oil and organic solvents in open water. An absorption capacity in the range 12–23 g g–1 for the test liquids light crude oil, engine oil, paraffin oil, chloroform, kerosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(98 reference statements)
1
8
0
Order By: Relevance
“…The sponge needed to be highly oleophilic, that is, an oil contact angle of <35° or having a surface energy (20–30 mJ/m 2 ) close to those of most hydrocarbon oils. Thus, a hydrocarbon agent would work better than a fluorocarbon agent in preparing porous media for absorbing most oils (e.g., diesel), agreeing with the results reported in a previous study . Also, to promote a rapid oil uptake, a superoleophilic medium that can be completely wet, that is, a 0° oil contact angle or a positive S value, by various oils is desirable.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The sponge needed to be highly oleophilic, that is, an oil contact angle of <35° or having a surface energy (20–30 mJ/m 2 ) close to those of most hydrocarbon oils. Thus, a hydrocarbon agent would work better than a fluorocarbon agent in preparing porous media for absorbing most oils (e.g., diesel), agreeing with the results reported in a previous study . Also, to promote a rapid oil uptake, a superoleophilic medium that can be completely wet, that is, a 0° oil contact angle or a positive S value, by various oils is desirable.…”
Section: Discussionsupporting
confidence: 87%
“…To selectively absorb only oil from an oil–water mixture, the focus has mostly been on fabricating materials that are superhydrophobic (with a water contact angle of >150° on the absorbent) and superoleophilic (with an oil contact angle of <15° on the absorbent) or superhydrophobic and oleophilic (with an oil contact angle of <90° on the absorbent). Many researchers have utilized hydrophobic polymers, such as polystyrene and polydimethylsiloxane, for the needed wettability. Other studies have incorporated fluoro materials to increase hydrophobicity. , In a recent review, Sam and co-workers summarized several methods for surface engineering sponges, including cellulose sponges, to improve their surface hydrophobicity, in particular, to change the sponges’ surface wettability to superhydrophobic and superoleophilic by using hydrophobic agents, such as organosilanes, , either alone , or in combination with other nanomaterials. , While superhydrophobic sponges are common in most studies, Minju et al have reported the use of hydrophobic alkylsilane modified sponges that had water contact angles between 100° and 125° and oil contact angles of ∼0° to selectively and completely absorb various oils from seawater. Hydrophobic foams of polyurethane modified with organosilane, having water contact angles of 105–110°, also resulted in a high oil collection capability in the study by Zimmermann et al These latter studies clearly illustrated that hydrophobic, not necessary superhydrophobic, sponges were sufficient for selective removal of oil from water.…”
Section: Introductionmentioning
confidence: 99%
“…porous absorbents (such as IOHS sponge, 38 PA 6/OMMT sponge 39 ). Although the GE aerogel showed higher Q value than PGPd-PU sponge, this type of absorbent was difficult to be used in large-area spilled oil remediation due to its complicated fabrication process and high cost.…”
Section: Characterization Of the Pgpd-pu Spongementioning
confidence: 99%
“…Frequent marine oil spills and the illegal discharge of oily wastewater have resulted in irreversible damage to the aquatic ecosystem and huge economic losses. The conventional treatments for oil spills involve in situ combustion, biodegradation, dispersion, adsorption, and solidification, whereas, the corresponding consumption is huge. Therefore, researchers have paid considerable attention to developing environmentally friendly and efficient methods for dealing with oil spills. Phase-selective organogelators (PSOGs) have recently attracted more attention because of their advantages in handling oil spills. PSOGs can self-assemble to form a three-dimensional network structure by noncovalent interactions, such as hydrogen bonding, hydrophobic interactions, van der Waals forces, π–π interactions, and electrostatic interactions, which endow PSOGs with the capacity to immobilize the oil phase. With additional research, the service conditions of PSOGs are becoming more straightforward and more convenient. , However, these methods for the subsequent treatment of reclaimed organic gels are still more complicated. , Hence, it is necessary to develop a simple and efficient method for the separation and recovery of the oil phase and organogelators.…”
Section: Introductionmentioning
confidence: 99%